Aquaporin-4 antibodies are not related to HTLV-1 associated myelopathy - Glehn, Felipe von; Jarius, Sven; Wildemann, Brigitte (PLOS ONE, 2012)
Introduction The seroprevalence of human T-cell leukemia virus type 1 (HTLV-1) is very high among Brazilians (∼1∶200). HTLV-1 associated myelopathy or tropical spastic paraparesis (HAM/TSP) is the most common neurological complication of HTLV-1 infection. HAM/TSP can present with an acute/subacute form of longitudinally extensive myelitis, which can be confused with lesions seen in aquaporin-4 antibody (AQP4-Ab) positive neuromyelitis optica spectrum disorders (NMOSD) on MRI. Moreover, clinical attacks in patients with NMOSD have been shown to be preceded by viral infections in around 30% of cases. Objective To evaluate the frequency of AQP4-Ab in patients with HAM/TSP. To evaluate the frequency of HTLV-1 infection in patients with NMOSD. Patients and Methods 23 Brazilian patients with HAM/TSP, 20 asymptomatic HTLV-1+ serostatus patients, and 34 with NMOSD were tested for AQP4-Ab using a standardized recombinant cell based assay. In addition, all patients were tested for HTLV-1 by ELISA and Western blotting. Results 20/34 NMOSD patients were positive for AQP4-Ab but none of the HAM/TSP patients and none of the asymptomatic HTLV-1 infected individuals. Conversely, all AQP4-Ab-positive NMOSD patients were negative for HTLV-1 antibodies. One patient with HAM/TSP developed optic neuritis in addition to subacute LETM; this patient was AQP4-Ab negative as well. Patients were found to be predominantly female and of African descent both in the NMOSD and in the HAM/TSP group; Osame scale and expanded disability status scale scores did not differ significantly between the two groups. Conclusions Our results argue both against a role of antibodies to AQP4 in the pathogenesis of HAM/TSP and against an association between HTLV-1 infection and the development of AQP4-Ab. Moreover, the absence of HTLV-1 in all patients with NMOSD suggests that HTLV-1 is not a common trigger of acute attacks in patients with AQP4-Ab positive NMOSD in populations with high HTLV-1 seroprevalence.